Effects of Core Muscle Training Program Using Progression Principle on Balancing and Receiving Skills in Beach Volleyball of Secondary School Students - Sawasworn, Sakda; Tingsabha, Suthana; Vathagavorakul, Ravisara (An Online Journal of Education, 2022)
The purposes of this study were 1) to compare balancing and receiving skills before and after of an experimental group, and 2) to compare balancing and receiving skills between an experimental group and a control group after implementation. Thirty students participated in the study. An additional 30-min core muscle training program was performed three days a week for eight weeks (on Mondays, Wednesdays and Fridays). The data were analyzed using mean, standard deviations and t-tests The findings were as follows: 1) the mean of the static balancing, dynamic balancing and receiving skill after treatment of the experimental group was higher than before the experiment at the significance level of .05; and 2) the mean of the static balancing, dynamic balancing and receiving skill after the experiment of the experimental group students was higher than the control group at a significance level of .05. Conclusion: a core muscle training program using progression principle leads the students to better static balancing, dynamic balancing and receiving skills in which they can use these skills to be excellent beach volleyball players.